Pengembangan Sistem Pendukung Keputusan Untuk Mendukung Penegakkan Diagnosa TB Dots Di Rumah Sakit Aisyiyah Muntilan - Susanti Susanti; Mateus Sakundarno Adi; Atik Mawarni (Jurnal Manajemen Kesehatan Indonesia, 2016)
Tuberculosis (TB) disease intervention is a national program and being a target of MDGs. Therefore, a government determined minimum service standards of a hospital that had to be implemented in all health service units and hospitals in Indonesia. A strategy of DOTS at Aisyiyah Hospital in Muntilan had been available particularly in terms of case finding. Notwithstanding, a process of patient diagnosis had not been implemented in accordance with a standard of human resource. Number of medical officers at a TB DOTS unit was not sufficient. In addition, quality of information like completeness, accurateness in diagnosis, and timeliness in reporting TB cases had not achieved a target. The aim of this study was to develop decision support system of TB as an effort to systematically diagnose and manage data of TB based on the standard. This was qualitative-quantitative research. A qualitative method was used to identify each step of information system development. Meanwhile, a quantitative method was used to assess quality of information between before and after developing information system using pre-experimental design (the one group pre and posttest design). Qualitative data were collected by conducting indepth interview, whereas quantitative data were collected using checklist. Data were analysed using T test. Research object was decision support system before and after applying at TB unit at Aisyiyah Hospital in Muntilan. Research subjects consisted of four TB officers as main informants. Informants for triangulation purpose consisted of head of SIMRS and head of medical services. The results of T test showed that variables of completeness, accurateness, and preciseness after developing the decision support system were better than that of before developing the system (p-value = 0.000). As suggestions, head of SIMRS needs to conduct further development of decision support system of TB in another unit particularly in inpatient unit. The decision support system needs to be evaluated and adjusted with the standard.